2017
DOI: 10.1038/s41598-017-13867-2
|View full text |Cite
|
Sign up to set email alerts
|

Catsper1 promoter is bidirectional and regulates the expression of a novel lncRNA

Abstract: The Catsper1 gene, whose expression is restricted to male germ cells, has great importance in reproductive biology because of its function in sperm motility and fertilization. We previously reported that the promoter of this gene has transcriptional activity in either direction in a heterologous system. In the present study, we found that the Catsper1 promoter has in vitro transcriptional activity in either orientation in GC-1 spg mouse spermatogonial cells. The results also showed that this promoter regulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…S7A). Together, this data provides evidence of regulated co-expression of the mRNA:lncRNA pair which has been observed in other, similarly organized, genes, and can form an aspect of transcriptional regulation (Kaur et al 2016; Yamamoto et al 2016; Jiménez-Badillo et al 2017; Malhotra et al 2017). Currently, we have no evidence of a regulatory inter-relationship at this bidirectional promoter site.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…S7A). Together, this data provides evidence of regulated co-expression of the mRNA:lncRNA pair which has been observed in other, similarly organized, genes, and can form an aspect of transcriptional regulation (Kaur et al 2016; Yamamoto et al 2016; Jiménez-Badillo et al 2017; Malhotra et al 2017). Currently, we have no evidence of a regulatory inter-relationship at this bidirectional promoter site.…”
Section: Discussionsupporting
confidence: 57%
“…We have also demonstrated that the rat Cacng2 promoter has a bidirectional organization (Adachi and Lieber 2002 ), involving antisense transcription of associated lncRNA(s). Bidirectional activity of the identified Cacng2 promoter sequence was functionally demonstrated here, using forward and reverse promoter constructs as for other, similarly oriented, gene pairs (Jiménez-Badillo et al 2017 ). Our finding is consistent with both the observed proximal initiation of the paired Cacng2 and lncRNA transcripts (generally within 2 kb in bidirectional promoter-associated, neuronal gene pairs, Hu et al 2014 ), and also with features such as the central CpG island (Uesaka et al 2014 ), and the absence of a TATA box (Lasagna Transfac analysis; Bagchi and Iyer 2016 ).…”
Section: Discussionmentioning
confidence: 84%
“…Of course, there is a complexity in Catsper1 gene expression, Catsper1 promoter is bidirectional and regulates the expression of a lncRNA (Catsper1au). Indeed, Catsper1au is expressed in adult male mouse testis and can regulate gene expression during spermatogenesis (49). It is possible that broccoli contains compounds that bind directly or indirectly to regulatory proteins that regulate this lncRNA or binds to the Catsper1au target site or some other unknown phenomenon involved in Catsper1 gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). (1) Intergenic lncRNAs originate from DNA sequences between two protein-coding genes, such as MALAT1 13 , Linc-ROR 14 , and ANCR 15 ; (2) intronic lncRNAs originate from introns of protein-coding genes, such as PRUNE2 16 , PCA3 17 , COLDAIR 18 , and SYISL 19 ; (3) sense lncRNAs overlap with one or more introns and exons of different protein-coding genes, such as LncRNA-GAS5 13 and ecCEPBA 20 ; (4) antisense lncRNAs originate from an opposite direction to a protein-coding gene, such as TALAM1 21 , PDCD4-AS1 22 , and Wrap53 23 ; (5) enhancer lncRNAs originate from the regions of promoter enhancer, such as LncRNA-LEENE 24 and Lnc-SLC4A1-1 25 ; and (6) bidirectional lncRNAs exist in proximity of a coding transcript of the opposite strand, such as Linc00441 26 and Catsper1au 27 . So far, lncRNAs have been shown to exert auxiliary functions either to tumor suppression or to tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%